PARENTHOOD AND CHILD DEVELOPMENT: ISLAMIC APPROACH TO RAISING NOBLE PERSONALITIES - Dr Dawood Adesola Hamzah (Journal of Islamic, Social, Economics and Development, 2019)
Children are Divine gifts. One of the ways to show and express appreciation to the Merciful Giver is to raise children to know and worship their Creator and to be useful members of their communities and the entire human race. To Muslims, Children are not only Divine gifts but also Trust (‘Amanah). To that extent, Muslim parents have responsibility to ensure that children are treated with kindness, protected and nurtured to become God-fearing, God- conscious, kind, dedicative, hard-working, productive and abundant assets to themselves, their families and ultimately to the Islamic Ummah. It is a challenging task to raise a child for future leadership. But, for parents who are focus and who are committed to observing and upholding the tenets of their faith, it is easy. Islamic processes of parenting are essentially based on the concept of Fitra. Fitra serves as a lunch-pad for the Islamic Tarbiya of a child. A proper observance of the Islamic approach, it is argued makes parenting an easy task. This work is an attempt to explore the processes of raising children within the framework of Islamic elucidation. It will examine the implications of some classical and modern approaches to child parenting and child development. For example, the issue of corporal punishment and the emergence of the internet and social media. Against this background, this study will seek to establish a synergy between Islamic and Western liberalism approaches to child parenting and development among young parents generally and particularly the Muslim families that are domicile in non-Muslim societies consequent to the emergence of multi-cultural and pluralistic societies.